Grewia optiva Fiber Reinforced Novel, Low Cost Polymer Composites - A. S. Singha; Vijay Kumar Thakur (E-Journal of Chemistry)
In this research article, the assessment of properties of compression molded Grewia optiva fiber reinforced Urea-Formaldehyde (UF) matrix based polymer composites is reported. Reinforcing of the UF resin with Grewia optiva fiber was accomplished in the particle, short and long fiber reinforcement. Present work reveals that mechanical properties such as: tensile strength, compressive strength and wear resistance of urea - formaldehyde resin increases to a significant extent when reinforced with Grewia optiva fiber. Analysis of results shows that particle reinforcement is more effective as compared to short and long fiber reinforcement. Morphological and Thermal studies of the matrix and fibre reinforced biocomposites have also been carried out